Dissection of 4L lymph node for left-sided non-small cell lung cancer: a meta-analysis - Li, Chenxi; Hu, Zhuozheng; Wu, Jiajun; Zhou, Weijun; Zhang, Wenxiong; Song, Chao (Frontiers in Oncology, 2025)
BackgroundThe therapeutic efficacy of left lower paratracheal (4L) lymph node dissection in the management of left-sided non-small cell lung cancer (NSCLC) remains an unresolved clinical question. Therefore, we conducted a meta-analysis to compare the survival of patients with left-sided NSCLC who underwent 4L lymph node dissection (LND+) and those who did not (LND−).MethodsSeven databases were searched for relevant studies comparing patients with left-sided NSCLC who underwent 4L lymph node dissection and those who did not. The primary endpoints were survival indicators, including overall survival (OS) and disease-free survival (DFS). Secondary endpoints included hospitalization and follow-up outcomes.ResultsAfter thoroughly screening 431 studies, six studies encompassing 4,253 patients were included in the final analysis. The LND+ group showed better OS (hazard ratio [HR]: 0.65 [0.52, 0.81], p < 0.0001) and DFS (HR: 0.82 [0.71, 0.95], p = 0.008). The 4L LND+ group also demonstrated higher OS rates at 1–5 years and DFS at 1 year. Postoperative complications and recurrence rates were similar between the two groups.ConclusionsBased on these results, 4L lymph node dissection should be performed for left-sided resectable NSCLC, due to its association with improved OS and DFS.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024567681, identifier CRD42024567681.